2002
DOI: 10.1152/ajpcell.00444.2001
|View full text |Cite
|
Sign up to set email alerts
|

Functional overload increases β-MHC promoter activity in rodent fast muscle via the proximal MCAT (βe3) site

Abstract: . Functional overload increases ␤-MHC promoter activity in rodent fast muscle via the proximal MCAT (␤e3) site. Am J Physiol Cell Physiol 282: C518-C527, 2002. First published October 24, 2001 10.1152/ ajpcell.00444.2001 of the rat plantaris muscle by the removal of synergistic muscles induces a shift in the myosin heavy chain (MHC) isoform expression profile from the fast isoforms toward the slow type I, or, ␤-MHC isoform. Different length rat ␤-MHC promoters were linked to a firefly luciferase reporter gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 36 publications
1
22
1
Order By: Relevance
“…Also, to rule out the possibility of interresearcher differences in technique or reagent variances, previous experiments of promoters that gave us high activity and were intervention responsive (e.g., type I MHC, myosin light chain kinase) were repeated in the process of collecting the data reported in this report (data not shown). These experiments resulted in responses similar to those reported previously (11,12,15) and thus confirmed the reliability and validity of the methods utilized here.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Also, to rule out the possibility of interresearcher differences in technique or reagent variances, previous experiments of promoters that gave us high activity and were intervention responsive (e.g., type I MHC, myosin light chain kinase) were repeated in the process of collecting the data reported in this report (data not shown). These experiments resulted in responses similar to those reported previously (11,12,15) and thus confirmed the reliability and validity of the methods utilized here.…”
Section: Discussionsupporting
confidence: 89%
“…To improve uptake of plasmids in the plantaris muscle, electropermeabilization was induced on the plantaris muscle immediately after plasmid injection. The electroporation procedure was applied with two gold-plated stainless steel electrodes delivered in four pulses of 200 V/cm for 50 ms each at 1 Hz, followed by four additional pulses of opposite polarity, as described previously (12). All experiments were carried out for 7 days, which was shown in prior pilot experiments to be within the time period of maximum promoter-reporter expression.…”
Section: Experimental Design and Animal Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Mutational analyses have revealed that functional overloadinduced activity of the ␤-MHC gene is mediated through the proximal MCAT element in rat plantaris muscle. 48 Moreover, denervation-induced decrease in ␤-MHC expression is also mediated by the proximal MCAT element in rat soleus. 49 Taken together, these results clearly indicate the contribution of the MCAT element to the regulation of muscle-specific genes in skeletal muscle.…”
Section: Skeletal Muscle Hypertrophy and Regenerationmentioning
confidence: 98%
“…The inability of these IGF-I promoter regions to drive more robust expression in vivo was not due to low levels of plasmid uptake, because a coinjected skeletal muscle ␣-actin promoter expressing the RLuc gene showed very high activity (ϳ400-fold higher than background) and increased by ϳ50% in FO plantaris. In addition, Giger et al (15) used the direct gene transfer approach to study regulation of the type I MHC promoter in overloaded skeletal muscle and reported an ϳ100-130% increase in the type I MHC promoter activity in FO plantaris.…”
Section: Discussionmentioning
confidence: 99%